Fluorescence-assisted visualization of facial nerve during mastoidectomy: A novel technique for preventing iatrogenic facial paralysis. Issue 2 (April 2015) - Chen, Shao-Ching; Wang, Mao-Che; Wang, Wei-Hsin; Lee, Cheng-Chia; Yang, Tsui-Fen; Lin, Chun-Fu; Wang, Jui-To; Liao, Chih-Hsiang; Chang, Chih-Chang; Chen, Min-Hsiung; Shih, Yang-Hsin; Hsu, Sanford P.C.
Highlights Facial nerve injury is one of the major morbidity during the mastoidectomy as the main or part of the different surgical approaches. In addition to familiarity with surgical anatomy and electrophysiological monitoring, ICG fluorescence-guided drilling of facial canal helps to reduce the risk of iatrogenic facial nerve injury and shorten the learning curve for beginners to identify and skeletonize the facial canal with safety.